Tenancy: attachment and residential vulnerability in the port district of Valparaíso - Marín Toro, Adriana (Revista INVI, 2017)
Current housing policies and the increased price of land hamper the construction of well-located dwellings for low-income groups in Chile. On the other hand, international recommendations propose the leasing of dwellings as a solution to the spatial segregation generated by housing policies. However, the situation of tenants and the activity of leasing as well as the housing policies involved in this sector have been scarcely explored in Chile and Latin America. The case study of the port district of Valparaíso, a site characterized by the development of this type of tenure –where more than 90 percent of dwellers are tenants– explores and describes the subjective dimensions of tenancy associated with attachment and the sense of belonging to the place of residence and the neighborhood, which transcend the type of land ownership. This paper analyses the characteristics of tenancy, which is understood as a specific type of residential vulnerability within a context marked by social production at a neighborhood scale and the pressure exerted by urban renewal and gentrification initiatives.